The law, economics and politics of international standardisation - Delimatsis, Panagiotis (Cambridge international trade and economic law, 2015)
"In an era of increased reliance on private regulatory bodies and globalised economic activity, standardisation is the field where politics, technical expertise and strategic behaviour meet and interact. International standard-setting bodies exemplify the rise of transnational governance and the challenges that it brings about relating to institutional choice, legitimacy, procedural and substantive fairness or transparency. This book takes a more empirical-based approach focusing on the mechanics of international standard-setting. It constitutes a multidisciplinary inquiry into the foundations of international standard-setting, an empirically under-researched yet important area of international informal lawmaking. Contributors expertly examine the peculiarities of international standardisation in selected issue-areas and legal orders and shed light on the attributes of international standard-setters, allowing comparisons among standard-setting bodies with a view to identifying best practices and improve our understanding about standardisation processes"--